2016
DOI: 10.1111/bdi.12388
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic shift in patients diagnosed with schizoaffective disorder: a systematic review and meta‐analysis of rediagnosis studies

Abstract: Diagnostic shift in SAD patients is substantial. Psychiatrists need to reassess the diagnosis during the course of the illness and to adjust treatment. Slightly more diagnoses of SAD are changed to schizophrenia than to affective disorders, and among patients rediagnosed with SAD, fewer have been diagnosed with schizophrenia than with affective disorders. Thus, at the diagnostic level, there seems to be a slight trend toward schizophrenia during the course of functional psychoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
(69 reference statements)
0
13
0
2
Order By: Relevance
“…The hazard ratio for psychotic depression to progress to SAD was exceptionally high, 10.6 (CI 95% 4.0-28.4). This finding may reflect the previously reported frequent shift from psychotic depression to SAD, 20 although the wide confidence interval indicates uncertainty in the actual size of the risk.…”
Section: Predictors For Diagnostic Conversionmentioning
confidence: 71%
See 1 more Smart Citation
“…The hazard ratio for psychotic depression to progress to SAD was exceptionally high, 10.6 (CI 95% 4.0-28.4). This finding may reflect the previously reported frequent shift from psychotic depression to SAD, 20 although the wide confidence interval indicates uncertainty in the actual size of the risk.…”
Section: Predictors For Diagnostic Conversionmentioning
confidence: 71%
“…Depressive symptoms and UD frequently precede both schizophrenia 11,18,19 and schizoaffective disorder (SAD), 20 and ultra-highrisk (UHR) patients often seek treatment due to depressed mood. UD per se appears to predict conversion to psychosis in UHR patients.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal stability of schizoaffective disorder, however, is markedly lower than that of its most important differential diagnoses, schizophrenia and affective disorders. Averaging the results of more than two dozen studies on the longitudinal course of SAD, we found that, at reassessment after on average 2 years, a solid third of patients with an initial diagnosis of SAD had switched to other diagnoses—mainly to schizophrenia (19%) and affective disorders (14%) 2 . It adds to the impression that, among those who received a diagnosis of SAD at reassessment, fully 55% had not been so diagnosed at baseline.…”
Section: Proxies For Validity: Temporal Stability and Position Relatimentioning
confidence: 60%
“…The nosological validity of SZA as a separate diagnosis is questioned and the diagnostic reliability is low (Jäger et al, 2010;Santelmann et al, 2015). Diagnostic shift over time is common (Fusar-Poli et al, 2016;Santelmann et al, 2016). SZA may reflect the co-occurrence of SZ and a mood disorder (Abrams et al, 2008), whereas others suggest a dimensional approach with SZA on a continuum between SZ and bipolar disorder (Keshavan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%